Pathological manifestations in lymphatic filariasis correlate with lack of inhibitory properties of IgG4 antibodies on IgE-activated granulocytes. - Ulrich F Prodjinotho; Charlotte von Horn; Alex Y Debrah; Linda Batsa Debrah; Anna Albers; Laura E Layland; Achim Hoerauf; Tomabu Adjobimey (Public Library of Science (PLoS), 2017)
Helminth parasites are known to be efficient modulators of their host's immune system. To guarantee their own survival, they induce alongside the classical Th2 a strong regulatory response with high levels of anti-inflammatory cytokines and elevated plasma levels of IgG4. This particular antibody was shown in different models to exhibit immunosuppressive properties. How IgG4 affects the etiopathology of lymphatic filariasis (LF) is however not well characterized. Here we investigate the impact of plasma and affinity-purified IgG/IgG4 fractions from endemic normals (EN) and LF infected pathology patients (CP), asymptomatic microfilaraemic (Mf+) and amicrofilaraemic (Mf-) individuals on IgE/IL3 activated granulocytes. The activation and degranulation states were investigated by monitoring the expression of CD63/HLADR and the release of granule contents (neutrophil elastase (NE), eosinophil cationic protein (ECP) and histamine) respectively by flow cytometry and ELISA. We could show that the activation of granulocytes was inhibited in the presence of plasma from EN and Mf+ individuals whereas those of Mf- and CP presented no effect. This inhibitory capacity was impaired upon depletion of IgG in Mf+ individuals but persisted in IgG-depleted plasma from EN, where it strongly correlated with the expression of IgA. In addition, IgA-depleted fractions failed to suppress granulocyte activation. Strikingly, affinity-purified IgG4 antibodies from EN, Mf+ and Mf- individuals bound granulocytes and inhibited activation and the release of ECP, NE and histamine. In contrast, IgG4 from CP could not bind granulocytes and presented no suppressive capacity. Reduction of both the affinity to, and the suppressive properties of anti-inflammatory IgG4 on granulocytes was reached only when FcγRI and II were blocked simultaneously. These data indicate that IgG4 antibodies from Mf+, Mf- and EN, in contrast to those of CP, natively exhibit FcγRI/II-dependent suppressive properties on granulocytes. Our findings suggest that quantitative and qualitative alterations in IgG4 molecules are associated with the different clinical phenotypes in LF endemic regions.